States of disorder: An ecosystems approach to state-building in conflict-affected countries - Adam Day (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
Why is the recent track record of state-building so poor? Over the past decade, international interventions in Afghanistan, Somalia, Central African Republic, Libya, Mali, South Sudan, and the Democratic Republic of the Congo have not resulted in meaningful improvements in the capacities of those countries to govern effectively and peacefully. In fact, there is a growing body of evidence to suggest that in many settings, state-building efforts may have contributed to conflict dynamics. This paper proposes an explanation based on complexity theory, employing an ecosystems lens to explain how systems of governance resist so-called external efforts to transform them into liberal models of the state. Instead of a gradual, linear progression towards improved state institutional capacity, governance systems in settings like South Sudan evolve, often shifting into more violent, predatory, and exclusive patterns of behaviour that undermine the United Nations' core objectives. These raise existential questions for peacebuilding as a practice, and for the United Nations as a protagonist in many of these settings.
Keywords: 330; state-building; peacebuilding; complexity; governance; United Nations